Programa resolución de problemas para mejorar el logro de aprendizaje cognitivo en estudiantes de la asignatura de matemática facultades agronomía y biología UNAP 2020 - Pongo Mendo, Enrique Gabriel (2023)
The objective of the research is to assess the effect of the problem resolution program in achieving learning in mathematics of the professional career of Agronomy , National University of the Peruvian Amazon, Iquitos 2018, the sample consists per 40 students of Agronomy in mathematics that are the experimental group and 40 career of biology students enrolled in the course of matematiza is the control group, used quantitative method, correlation, application level, in a quasi-experimental pre test, post test control group design. The following results were obtained: in the pre test, most reached 55% achievement at home and in the post test reached the achievement process (B) with an average of 11.075 points. In the pre test, the level of learning in the experimental group is equal to the level of learning in the control group before applying the problem-solving program. In the post test learning level are equal the experimental group as the control group. In the pre test, the level of learning in the experimental group is different to the level of learning achieved by students in the experimental group after applied problem solving program. Not met achievement outstanding or efficient in the cognitive, procedural and attitudinal. In the experimental group in the Post test, 7.5% obtained expected accomplishment (A), 82.5% achievement in process (B), and 10% achievement at home (C), with average of 11.075 points equal to achievement in process (B). In the group control the 12.5% achieving (A), 50% for the achievement in process (B), and 37.5% for the achievement in home (C), with average of 9.4 points, equivalent to achievement in home (C).